Impatiens glandulosocalycina (Balsaminaceae), a new species with glandular-aristate lateral sepals from Yunnan, China - He, Qiao-Sheng; Zhang, Ding-Can; Hu, Tian; Pan, Xiang-Tao; Cong, Yi-Yan; Hu, Guang-Wan (Phytotaxa, 2025)
Impatiens glandulosocalycina, a new species from Yingjiang County, Yunnan, China, is described and illustrated. This species is assigned to I. sect. Racemosae based on the combination of diagnostic morphological characters including racemose inflorescences with 6–12 flowers, two lateral sepals and linear fruit. Morphologically, the new species resembles I. aquatilis and I. uliginosa in having alternate leaves, lanceolate leaf blades, two glands at petiole base and racemose inflorescences, but can be distinguished from them by its sparsely setose stem, ovate-lanceolate bracts, broadly ovate lateral sepals, broadly reniform dorsal petal, clawed lateral united petals with ovate-oblong basal lobes and long lanceolate distal lobes, and deeply saccate lower sepal with a shorter spur.